Model for reducing defective production of PET Bottles through Lean Manufacturing (LACCEI, 2024)
This article aims to bring out the importance of reducing defective products in a company that blows polyethylene terephthalate preforms for the manufacture of plastic bottles located in the city of Huanuco in Peru. The problem that arises with the generation of defective products is that they harm the economic and environmental aspects. Therefore, this article proposes a model for the reduction of defective production through the application of Lean Manufacturing tools. This model was developed mainly using SMED and TPM tools. In addition, integrating other tools such as FMEA and 5S was considered to achieve better results in reducing defective production in the company and thus eliminate the economic losses they cause. The model was validated using simulation software, and only for the 5S was a pilot carried out the results obtained were a reduction in the level of defective production by 2.41% due to improvements in maintenance management and work methods.